2015
DOI: 10.1002/acn3.203
|View full text |Cite
|
Sign up to set email alerts
|

AlteredPLP1splicing causes hypomyelination of early myelinating structures

Abstract: ObjectiveThe objective of this study was to investigate the genetic etiology of the X-linked disorder “Hypomyelination of Early Myelinating Structures” (HEMS).MethodsWe included 16 patients from 10 families diagnosed with HEMS by brain MRI criteria. Exome sequencing was used to search for causal mutations. In silico analysis of effects of the mutations on splicing and RNA folding was performed. In vitro gene splicing was examined in RNA from patients’ fibroblasts and an immortalized immature oligodendrocyte ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…Consistent with the detection of normal lineage specification, we did not detect any upregulation of neuronally enriched gene categories. Because OL differentiation is characterized by alternatively spliced events (Kevelam et al, 2015; Nave et al, 1987), we interrogated our RNA-Seq dataset in control and mutant cells (Figure 7A). It has been suggested that DNA methylation in specific genomic regions is critical for exon skipping and intron retention splicing events (Gelfman et al, 2013; Yearim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the detection of normal lineage specification, we did not detect any upregulation of neuronally enriched gene categories. Because OL differentiation is characterized by alternatively spliced events (Kevelam et al, 2015; Nave et al, 1987), we interrogated our RNA-Seq dataset in control and mutant cells (Figure 7A). It has been suggested that DNA methylation in specific genomic regions is critical for exon skipping and intron retention splicing events (Gelfman et al, 2013; Yearim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that aberrant splicing might change protein conformation (Kevelam et al, 2015; Yura et al, 2006), and lead to the potential accumulation of incorrectly folded proteins inducing endoplasmic reticulum (ER) stress. Consistent with this possibility we observed dilated ER in mutant oligodendrocytes, with characteristic and unique electron-dense inclusions (Figure 7F), suggestive of protein accumulations and activation of ER stress response.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral neuropathy, central hypomyelination, Waardenburg-Hirschsprung [ 36 ] c. Early-onset neuronal degenerative disorders c. Cx47-related Pelizaeus-Merzbacher-like disease [ 36 ] 1. Gangliosidosis GM1 and GM2 [ 75 , 250 ] d. Hypomyelination of early myelinated structures [ 104 ] 2. Infantile neuronal ceroid lipofuscinosis [ 79 ] Demyelination 3.…”
Section: A Novel Classification Of Genetic White Matter Disorders Basmentioning
confidence: 99%
“…The lab improved their methods, went back to all their PLP1 negative patients and found more patients with cryptic alterations in this region. Further, careful review of the neuro-imaging of this patient contributed to the discovery of a novel PLP1 related phenotype termed hypomyelination of early myelinating structures (HEMS) caused by abnormal PLP1/DM20 alternative splicing due to exon 3 and intron 3 mutations (Kevelam et al 2015 ), further clarifying the precise relationship between gene mutation and phenotype and contributing to disease stratification. In vivo technologies such as nuclear magnetic resonance spectroscopy, radiolabeled isotype analysis to measure metabolic flux, and continuous glucose monitoring offer unique opportunities for deep phenotyping.…”
Section: Multi-omics In the Clinical Care For Imdsmentioning
confidence: 99%